Analyzing dynamic capability in teamwork - Gonzalez, Rodrigo Valio Dominguez; Melo, Tatiana Massaroli [UNESP] (Emerald, 2019)
Purpose: This study aims to analyze the relationship between the intrinsic characteristics of the teams that perform specialized industrial services in multi-units and dynamic capability. Design/methodology/approach: This study was developed from a survey conducted in 188 multi-unit industrial service providers and data were analyzed using the structural equation modeling technique of partial least squares. Findings: The results indicate the two constructs act differently on dynamic capability. While the infrastructural construct influences the capability of knowledge absorption, generation and adaptation, the construct related to the willingness to share and integrate knowledge has a positive impact on the capability of knowledge generation and storage. Research limitations/implications: This research is limited by the choice of only one industrial sector – in the case of this study, the service industry. Future studies will include other industries and a more diverse sample of firms. Originality/value: This research analyzes the process of dynamic capability development in the context of multi-unit service provision. The context of multi-unit industrial service provision is peculiar when compared to other organizations. In the context, knowledge is absorbed, generated and adapted by individuals organized into teams that work in customer’s units. Service providers play a key role in the development of dynamic capabilities regarding knowledge storage, acting as knowledge repositories.
Keywords: Dynamic capability; Knowledge management; Knowledge-based system dynamic capability; Multi-unit service; Structural equation modeling; Teamwork